Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/978-3-642-16435-4_2
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Submodular Framework for Multimodal IC Trojan Detection

Abstract: Abstract. This paper presents a unified formal framework for integrated circuits (IC) Trojan detection that can simultaneously employ multiple noninvasive measurement types. Hardware Trojans refer to modifications, alterations, or insertions to the original IC for adversarial purposes. The new framework formally defines the IC Trojan detection for each measurement type as an optimization problem and discusses the complexity. A formulation of the problem that is applicable to a large class of Trojan detection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Among them, side-channel based HT detection based on power and delay monitoring has become the most focused area [2,3,10,11,12,21]. However, until now, there are no standard and publicly accepted test benchmarks for evaluating the various side-channel-based HT detection solutions, making it difficult for IC design companies or researchers to select the most effective HT detection solutions or to compare them.…”
Section: Motivationmentioning
confidence: 99%
“…Among them, side-channel based HT detection based on power and delay monitoring has become the most focused area [2,3,10,11,12,21]. However, until now, there are no standard and publicly accepted test benchmarks for evaluating the various side-channel-based HT detection solutions, making it difficult for IC design companies or researchers to select the most effective HT detection solutions or to compare them.…”
Section: Motivationmentioning
confidence: 99%
“…Similar methods can be applied to linearly relate the overall measured quiescent and transient current modalities to gatelevel values. For the sake of brevity, we refer the readers to earlier literature [10], [20].…”
Section: ) Timing Modalitymentioning
confidence: 99%
“…An earlier version of this work appeared in [20]. The new aspects of this paper include sensitivity analysis and cumulative unimodal profiling.…”
Section: Related Workmentioning
confidence: 99%
“…For example, it has been shown that the Trojan detection objective function can be written in a submodular way, such that for a certain given set of Trojan test vectors, no algorithm can found a better solution within 63% of the optimal detection [6]. Any Trojan outside this bound would stay undetected by the detections that use the set of given test vectors.…”
mentioning
confidence: 97%
“…A novel suit of security and trust solutions based on process variation, design variability, and unique integrated circuits signatures is emerging [2][3][4][5][6][7][8][9][10][11]. The new methods are elegant yet practical, while they also provide low power and low cost security solutions.…”
mentioning
confidence: 99%